1996
DOI: 10.1038/bjc.1996.569
|View full text |Cite
|
Sign up to set email alerts
|

A phase I clinical trial of imiquimod, an oral interferon inducer, administered daily

Abstract: Summary Imiquimod is an orally active interferon inducer with anti-tumour activity in experimental animals. In this study the tolerability, toxicity and biological effects of daily oral imiquimod administration were investigated in 21 patients with refractory cancer. Patients were treated with doses of 25 mg, 50 mg, 100 mg or 200 mg on a projected 112 day course. Only three patients completed the course, all at the 50 mg dose.Treatment toxicities were dose related and mainly comprised flu-like symptoms, nausea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 14 publications
0
80
0
Order By: Relevance
“…Although f1/3 of patients had adverse events of severe intensity, and doselimiting toxicities occurred at 0.6 and 0.9 mg/m 2 , the overall safety profile was deemed tolerable, given the underlying disease. Although limited by the patient number and historical comparison, the gastrointestinal adverse events observed in this study seemed to be less frequent and/or less severe than observed in clinical studies of oral administration of imiquimod or resiquimod (19,20). The intestinal tract contains a large number of immune cells, including dendritic cells, and TLR7 expression has been reported on hepatocytes (21,22).…”
Section: Discussionmentioning
confidence: 88%
“…Although f1/3 of patients had adverse events of severe intensity, and doselimiting toxicities occurred at 0.6 and 0.9 mg/m 2 , the overall safety profile was deemed tolerable, given the underlying disease. Although limited by the patient number and historical comparison, the gastrointestinal adverse events observed in this study seemed to be less frequent and/or less severe than observed in clinical studies of oral administration of imiquimod or resiquimod (19,20). The intestinal tract contains a large number of immune cells, including dendritic cells, and TLR7 expression has been reported on hepatocytes (21,22).…”
Section: Discussionmentioning
confidence: 88%
“…It is known that double-stranded RNA, produced during a variety of viral infections, can induce transcription of IFN-␣/␤ genes, but nonviral inducers have also been described (4,36,41). Induction of the IFN␤ gene has been extensively studied in cell culture, leading to a detailed knowledge of cis-acting sequences and binding factors required for transcriptional induction (16); a similar but less complete analysis of IFN-␣ induction has been carried out (27).…”
mentioning
confidence: 99%
“…Imiquimod, a TLR7/8 agonist, has seen extensive clinical use (3,5) as a topical chemotherapeutic and antiviral. Experimental therapies employing TLR7 agonists have also demonstrated some clinical benefit in viral hepatitis (49), however, adverse immunologic events related to widespread biodistribution were observed at therapeutic doses (50,51) including unacceptable toxicity in a human trial of oral imiquimod (52). No adverse effects were observed in mice injected with LRNPs in this study, though long-term and dose-response effects of LRNP administration need to be investigated.…”
Section: Discussionmentioning
confidence: 73%